فنون العمارة الهندسية بمصر في عهد الدولة الحديثة - مياطة, التجاني (University of Eloued جامعة الوادي, 2019)
ملخص: العمارة هي كلمة من أصل كلمة عمر، وهي تشمل كل ما هو على وجه الأرض من مباني ومنشآت ومساكن سواء كانت من إنتاج متخصصون أو غير متخصصون، أما في اللغة العربية بكسر العين هي التشييد بالبناء، وهي مشتقة من عمر، أي سكن والمكان العامر هو المكان الآهل بالسكان، العمارة هي فن المباني وفق قواعد جمالية وهندسية ورقمية محددة، إلا أن هذا الفن هو فن اجتماعي، إذ تنظم العمارة المجالات وتنجزها، ليلجأ إليها الناس في حياتهم وفي أعمالهم لتكون إطار ترفيههم وهي لا تقف عند حدود الحدث المعماري البارز أو المعلم المميز، و هي تتناول الملجأ والمأوى البسيط، والأثاث وكل المقتنيات الضرورية لحياة الإنسان اليومية. Abstract: Architecture is a word out of the word Omar, which includes everything that is on the face of the earth buildings, installations and housing, whether produced by specialists or non-specialists, but in Arabic broken eye is the construction of construction, which is derived from Omar, any housing and place is the place People, architecture is the art of buildings according to specific aesthetic, engineering and digital rules, but this art is a social art, as the architecture organizes areas and accomplishes, to be used by people in their lives and in their work to be the framework of their entertainment and they do not stop at the borders of the landmark architectural event or distinctive teacher It deals with shelter, simple shelter, furniture and all the possessions Necessary for the daily life of human data.
مقال
Keywords: الكلمات المفتاحية: العمارة، الهندسة المعمارية، الأثار المصرية، المعابد الدينية، العمران المدني، المباني العسكرية. ; key words: Architecture, architecture, Egyptian monuments, religious temples, urban construction, military buildings.